Investigating the relationship between favorable urban space with the ritual of mourning case study: Muharram mourning ceremonies in Khatib neighborhood in Tabriz - Mahdi Alilu; elham kazemi; Mohammadreza Pourmohammadi (نشریه جغرافیا و برنامه‌ریزی, 2020)
City is the most important habitat for the man and the greatest cradle of civilization. Due to this fact, studying this phenomenon is of paramount importance. The problem today is that in the contemporary society many of Islamic traditions have been neglected. The impact of religious values on the construction of city spaces is of even greater importance. Cities are created according to ideologies and worldviews and the most sublime example of space occupation is Islamic beliefs and values. The mosque in an Islamic city, for instance, has been a site of political, nonmilitary, legal and economic gatherings. Nowadays, some religious rituals and ceremonies are held in spaces other than mosques and due to the paucity of favorable and appropriate space in the cities, streets and roads are occupied and traffic problems created. 200 students participated in this study and a close-ended questionnaire with a rating scale of 5 was used to gather data.  In this article I have tried to emphasize the necessity of holding religious rituals out of mosque space, and suggest and provide the procedures needed for the definition and formation of appropriate spaces for the aforementioned rituals and ceremonies.